Od tożsamości do utożsamienia. Inspiracja psychoanalityczna - Świrek, Krzysztof (Człowiek i Społeczeństwo, 2017)
Modern subject is interested in studying his or her identity, however this act of examination nullifies its object: showing it as problematical or even non-existent, impossible to maintain as coherent entity. As time passes, the problem radicalizes itself, as it is shown in the works of theoreticians of ‘late modernity’: identity is often treated as a project, non-conclusive process of seeking the optimal states of well-being. As the various ‘identity crises’ go on, it is stated in various ways, that even subjectivity itself is waning. Maybe focusing on individual, as someone who has particular identity is not the best way of entangling this knot of problems. Interesting inspirations come from psychoanalysis. Firstly, psychoanalytical theory shows us, that individual with particular traits is not the same, as subject, and that subject is always-already ‘deconstructed’, divided. Secondly, problems with identity may be elucidated, when we turn to psychoanalytical theories of identification. In fact, what we often call ‘identities’ is better to be understood as partial and even theatrical identification with some content. The article shows how certain concepts of Freud and Lacan can be used to clarify complex or even obscure problems that haunt the notion of ‘identity’ as a source of meaning, used by social sciences. Krzysztof Świrek, Od tożsamości do utożsamienia. Inspiracja psychoanalityczna [From Identity to Identification. Psychoanalytical Inspiration] edited by E. Smolarkiewicz, J. Kubera, „Człowiek i Społeczeństwo” vol. XLIV: Tożsamość i identyfikacje. Propozycje teoretyczne – doświadczenia badawcze [Identity and identifications. Theoretical proposals – research experiences], Poznań 2017, pp. 33-48, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.